THE IMPACT OF SLEEP DISORDERS ON CELLULAR IMMUNE REGULATION AMONG UNIVERSITY STUDENTS - AL-Ukaily, Hussein Ali Mohammed; Al-Saadi, Zainab Nashaat Shukur (PT. Antis International Publisher, 2025)
Objective: Sleep is a fundamental biological process that contributes to regulating physiological balance within the body, particularly in maintaining the efficiency of the immune system. Recent literature indicates that sleep disturbances, especially chronic ones, may lead to impaired cellular immune function and increased general inflammatory activity. Based on this hypothesis, this study aimed to evaluate the impact of sleep disturbances on cellular immune regulation in university students by analyzing lymphocyte ratios and concentrations of certain immune cytokines in the blood. Method: The study included (60) male and female students aged (19–24) years, divided into two groups: a group with sleep disturbances (n = 30), identified based on the Pittsburgh Sleep Quality Index questionnaire (PSQI ≥ 6), and a control group (n = 30) with normal sleep patterns. Immune cell ratios (CD3+, CD4+, CD8+, and CD56+) were measured using flow cytometry, while the concentrations of the cytokines IL-6, TNF-α, and IFN-γ were determined using enzyme-linked immunosorbent assay (ELISA). Result: The results showed a significant decrease in the percentages of CD3+, CD4+, and CD56+ cells in the sleep disorder group compared to the control group (p < 0.01), while no significant differences were recorded in the percentages of CD8+ cells. Regarding cytokines, a significant increase in the concentrations of IL-6 and TNF-α was found in those with sleep disorders (p < 0.01), while there was no significant difference in the level of IFN-γ. The study also revealed a moderate positive correlation between PSQI scores and IL-6 concentrations (r = 0.58, p < 0.01), indicating that poor sleep quality is associated with increased immune inflammation. Novelty: These findings highlight the negative biological impact of sleep disturbances on cellular immune function in young university students, and suggest a potential causal relationship between poor sleep quality and the activation of inflammatory pathways.